Borders and overflows of the criticism of objectivity in the training of Social Work professionals - Lobos, Nicolás Alberto (Critical Proposals in Social Work, 2023)
In this article we will try to put back on the table the epistemological and empirical need of objectivity for any discourse with pretensions of producing knowledge, in social sciences in general and in Social Work in particular. To this end, we will try to identify the edges and overflows of some critical theories that are frequently raised in the faculties of social sciences and, on the other hand On the other hand, based on the work of Saul Karsz, we will point out the false equivalence between objectivity and neutrality and between objective and indisputable. In reality, what is claimed to be indisputable is any dogma or ideological, political, scientific or militant affirmation that is pronounced as the "word of God". Objectivity, on the contrary, is a process of argumentative production, by definition debatable, basically rectifiable and generally collective (or, at least, involving more than one professional). We will try to explain how "neutrality is neutrality is impossible but objectivity is indispensable" (Karsz, 2017).